Q: What is 2x - 6 x 5?

Write your answer...

Submit

Still have questions?

Continue Learning about Other Math

If 2x + 5 = 11, then 11 - 5 = 2x 6 = 2x 3 = x

The given expression is x + 6 = 2x + 5. Subtract both sides by x to get: x - x + 6 = 2x - x + 5 6 = x + 5 Subtract both sides by 5 to get: 6 - 5 = x + 5 - 5 x = 1

2x -6 = 4 then 2x = 4 +6 x=10/2 = 5

4x - 7 = 2x + 5 2x - 7 = 5 2x = 12 x = 6.

x=1 2/3 How?: 2x-4+3 = 5x-6 2x-1 = 5x-6 2x-1+1 = 5x-6+1 2x = 5x-5 2x-5x = 5x-5x-5 -3x = -5 -3x/-3 = -5/-3 x = 5/3 x = 1 2/3

Related questions

2x - 6 = x + 5 Isolate x. 2x - x = 6 + 5 x = 11

If 2x + 5 = 11, then 11 - 5 = 2x 6 = 2x 3 = x

2x-6=x+5 2x -x=6+5 x=11 Check the math.

2x-6=4 6+4=2x 10=2x 10/2=x 5=x x=5

The given expression is x + 6 = 2x + 5. Subtract both sides by x to get: x - x + 6 = 2x - x + 5 6 = x + 5 Subtract both sides by 5 to get: 6 - 5 = x + 5 - 5 x = 1

2x-5=3x+6 -5-6=3x-2x -11=x x=-11

2x - 6 = 4 2x = 4 + 6 = 10 x = 10/2 = 5 ∴ x = 5

2x - 6 = 4 2x = 4 + 6 = 10 x = 10/2 = 5 ∴ x = 5

To solve this equation we have to isolate and solve for x. So: 2x-6= x+5 +6 +6 2x = x+11 -x -x x = 11 So x=11.

x2 - 2x - 5 = 0 x2 - 2x + 1 = 6 (x - 1)2 = 6 x - 1 = ± √6 x = 1 ± √6

5x+6-2x=-5-x 3x+6=-5-x 4x=-11 x=11/-4

2x -6 = 4 then 2x = 4 +6 x=10/2 = 5